Aura e reprodutibilidade técnica no pensamento estético de Walter Benjamin - Soraya Aguiar Ventura (2007)
The objective of this dissertation is to examine the phenomenon described by Walter Benjamin as the the declining aura of art in the modernity and articulating his emphasis on the Theory of Experience. According to Benja min, the extinction of traditional elements in the modern society has ultimately diminished the capability of human experiences. This situation is implicit in the treatment of public artwork, which reduces the human experience by limiting, and sometimes, completely blocking any possibility of experiential contact with art. Keeping in mind the Benjamins concept of relating the function of memory and the tradition to art history to the direction human existence in society, this text will to deepen, in particular, the relationship between four of his texts: Small History of Photography (1931) e The Artwork in the Age of Mechanical Reproduction (1935), The Narrator (1936) e About Some Motives in Baudelaire (1939). For us, the relationship between these texts is as complementary and at the same time, conflicting, seeing that each volume interacts helping us clarify obscures points. Yet, individually they sometimes confront us with an ambiguous argument, which affirms Benjamins thoughts about the declining aura of art.